On the possible mantle nature of the long-wave Central-European magnetic anomaly - I.K. Pashkevich; M.I. Orlyuk; A.V. Marchenko; A.A. Romanets; T.A. Tsvetkova; I.V. Bugayenko (Геофизический журнал, 2020)
This paper presents the results of a comprehensive analysis of geological and geophysical data, carried out to substantiate the existence and nature of transition class of magnetic anomalies produced by the Earth’s core and the lithosphere. This class of anomalies with a wavelength of 2000—4000 km belongs to the overlap region of the geomagnetic field spectra of the core and the lithosphere, and therefore their separation is arbitrary. The original technology of identifying the lithospheric component developed by the authors is based on one of the fundamental principles of geomagnetism — the change in time and space of the Earth’s core field and the stable position of the lithospheric anomalies.